Validated capillary electrophoretic assays for disaccharide composition analysis of galactosaminoglycans in biologic samples and drugs/nutraceuticals - Asimakopoulou, A. P.; Malavaki, C.; Afratis, N. A.; Theocharis, A. D.; FN Lamari; Karamanos, N. K. (Methods Mol BiolMethods Mol Biol, 2015)
Capillary electrophoresis is a separation technique with high resolving power and sensitivity with applications in glycosaminoglycan analysis. In this chapter, we present validated protocols for determining the variously sulfated chondroitin or dermatan sulfate-derived disaccharides. These approaches involve degradation of the polysaccharides with specific chondro/dermato-lyases and electrophoretic analysis with capillary zone electrophoresis in a low pH operating buffer and reversed polarity. This methodology has been applied to drug/nutraceutical formulations or to biologic samples (blood serum, lens capsule) and has been validated. Analysis of biologic tissue samples is often more demanding in terms of detection sensitivity, and thus concentration pretreatment steps and/or a derivatization step with 2-aminoacridone are often advisable.
Keywords: Aminoacridines; Carbohydrate Conformation; Chondroitin Sulfates/analysis/blood/chemistry; Chondroitinases and Chondroitin Lyases/metabolism; Dermatan Sulfate/analysis/chemistry; Dietary Supplements/*analysis; Disaccharides/*analysis/chemistry; Electrophoresis, Capillary/*methods; Humans; Lens Capsule, Crystalline/metabolism; Pharmaceutical Preparations/*chemistry; Polysaccharides/*analysis/blood/chemistry; Reproducibility of Results